Beban tugas guru sekolah menengah di daerah Batu Pahat, Johor Darul Takzim - Abdul Rahim, Azita (2012)
This research was conducted to determine the level of workload born by the teachers in Batu Pahat District. This study involved five schools in the District of Batu Pahat, the SMK Dato Seth, SMK Yong Peng, SMK Tun Ismail, SMK Senggarang and SMK Tunku Mahmud Iskandar. A total of 225 people the number of teachers were chosen as respondents in this study. The data were collected using a questionnaire consisted of four parts studied, (1) demography, (2) teacher workload, (3) teachers complaint and dissatisfaction and (4)actions taken by the administrator to reduce the workload. The data collected were then analyzed using descriptive statistics (mean, average and percentage). The findings showed that the teachers’ workload and complaints were scored at high level. Meanwhile the study showed that actions taken by the administrator to reduce the workload was scored at moderate mean level. Some suggestions were proposed to improve the situation based on the findings in this study.